QoS Matching Offset Oriented Resource Clustering Scheduling Algorithm in Grid Environment - Fang Dong; Junzhou Luo (Proceedings of the 2007 11th International Conference on Computer Supported Cooperative Work in Design : April 26-28, 2007 Melbourne, Australia, 2007)
With more and more research carried on in the QoS of Grid, QoS-based Grid task scheduling algorithm has become a hot research aspect. In this paper, various existing QoS-based Grid scheduling algorithms are analyzed firstly. And by introducing the conception of QoS matching offset between tasks and resources in Grid scheduling, resources and tasks can be clustering upon their offset in order that the resources in scheduling are able to be allocated on demand. Meanwhile, we take into consideration some parameters in the scheduling like QoS benefit value obtained by the task and some restricted condition: deadline of the task. The simulation results show that the algorithm's performance is better than most of the proposed algorithms in the aspects of effective resource utility, resource load balance, task acceptance rate and average QoS benefit value.